Representation of Muslims in William Shakespeare’s Othello - Altabaa, Homam; Mohamad Nasir, Maryam Shofia (2022)
Muslims in Western writings are usually attributed distorted images and negative characteristics by the writers. It has become a great concern that the misrepresentation of Muslims in Western writings influences the readers’ perception of Islam and Muslims, thus contributing to Islamophobia that is still prevalent in the present world. The history of misrepresentation of Muslims in Western literary writings dates back to centuries ago seeing how canonical writers like Thomas Dekker and Christopher Marlowe perpetuated the negative representations of Muslims characters in their works. This study attempts to shed light on the images and portrayals of Muslims in Othello (1603-1604), a play written by William Shakespeare during the early Elizabethan period. In order to conduct an in-depth analysis of this topic, this study employs the theory of postcolonialism, particularly adopting one of its prominent concepts, Orientalism as the main theoretical framework. The results of the analysis suggest that Shakespeare uses the Orientalist stereotypes of Muslims in the construction of the Moor and the Turks in the play. This study contributes to the future discussion of the Anglo-Islamic relations and the representation of Muslims in Elizabethan plays.